Respuesta :

.4 im pretty sure, correct me if I’m wrong.

Answer:

[tex]\boxed {d = \sqrt{29}}[/tex]

Step-by-step explanation:

Use the Distance Formula to help you determine the distance between the two given points:

[tex]d = \sqrt{(x_{2} - x_{1})^{2} + (y_{2} - y_{1})^{2}}[/tex]

First point: [tex](x_{1}, y_{1})[/tex]

Second point: [tex](x_{2}, y_{2})[/tex]

-Apply the given points onto the formula:

First point: [tex](6, 2)[/tex]

Second point: [tex](1, 0)[/tex]

[tex]d = \sqrt{(1 - 6)^{2} + (0 - 2)^{2}}[/tex]

-Solve for the distance:

[tex]d = \sqrt{(1 - 6)^{2} + (0 - 2)^{2}}[/tex]

[tex]d = \sqrt{(-5)^{2} + (-2)^{2}}[/tex]

[tex]d = \sqrt{25 + 4}[/tex]

[tex]\boxed {d = \sqrt{29}}[/tex] (Since the number cannot be square rooted, it would stay the same)

Therefore, the distance is [tex]\sqrt{29}[/tex].